ANALISIS HUBUNGAN FITUR DAN HARGA PADA PRODUK TAS HEWAN TERHADAP MINAT BELI KONSUMEN - Claudia Glory Marchatmyna; Meirista Wulandari (Jurnal Ilmiah Teknik Industri, 2025)
The trend toward increased pet ownership is driving demand for supporting products such as pet bags that are not only functional but also comfortable. Pawfect Organizer Bag is a pet bag product for small breeds of dogs and cats. In an effort to assess the behavior of pet owners, research waas conducted on their purchasing preferences for pet bags. The research aims to analyze the influence of product comfort features and price on consumer purchasing interest in pet bags. The method used a quantitative approach through the distribution of questionnaires to 50 respondents who are pet owners. The data underwent validity and reliability testing, F-tests, and T-tests to determine the significance between variables. The results of testing and data analysis showed that all research instruments were valid and reliable. The F test yielded a Sig value of 0.00 for comfort features and price, indicating that both variables simultaneously had a significant effect on purchase interest. The T test yielded a Sig value of 0.003 for price and a Sig value of 0.035 for comfort features. This indicates that both variables contribute partially to increasing consumer purchase interest, with the price variable being the dominant factor. Based on the test results, there are suggestions that Pawfect Organizer Bag manufacturers can implement to increase consumer purchase interest, namely by optimizing product comfort features and creating pricing strategies.